A new species of Heliogomphus from Vietnam (Odonata: Gomphidae) - Kompier, Tom; Karube, Haruki (Zootaxa, 2019)
Heliogomphus bidentatus sp. nov. (holotype male: Tam Dao National Park, Vinh Phuc Prov., northern Vietnam) is described from north and central Vietnam. This new species is similar to H. scorpio (Ris, 1912), but can be separated by the coloration of the thorax and details of the male caudal appendages. Information on its biology and ecology is provided.